Konflik Sosial Di Kampung Buatan II Kecamatan Koto Gasib Kabupaten Siak: (Studi Tentang Konflik Lahan Antara Masyarakat Dengan PT. WSSI) - Anisha Rahayu; Hesti Asriwandari (Lembaga Pengembangan Kinerja Dosen, 2023)
Research conducted in Kampung Buatan II, Koto Gasib District, Siak Regency. This conflict occurs because there is a source of conflict that makes this conflict appear continuously. There are demands for land, the use of wood and environmental damage. This research aims to explore and collect information about social conflict, namely the sources of social conflict that arise between the people of Kampung Buatan II and the plantation company PT. Wahana Subur Sawit Indah (WSSI) vehicle and to find out about the efforts made in the process of resolving social conflicts between village communities and the plantation company PT. Wahana Subur Sawit Indah (WSSI) vehicle. This research uses descriptive qualitative research methods. With a total of five subjects, they were also involved in the conflict that occurred, then it was the native people of the village who knew about the conflict and felt capable of defining and explaining a process of solving the problem based on existing facts. For data collection used were observation techniques, in-depth interviews and documentation. The theories used are conflict theory and social movement theory. Research in the field found that land conflicts were caused by companies not carrying out obligations that should be fulfilled by the company, as well as the emergence of Timber Utilization Permits (IPK), which then became a debate that led to conflict until now. The community has made various efforts to resolve the conflict, but the company still does not heed the things that have been agreed upon. Oil palm plantation companies and communities are always a record of cases of conflict that always exist and land conflicts are also classic problems and tend to drag on throughout the year.